The United Nations and the development of collective security the delegation by the UN Security Council of its chapter VII powers - Sarooshi, Dan (Oxford monographs in international law, 1999)
"This book examines one of the most important challenges facing the United Nations today: the effective and lawful use of force by or under the authority of the UN to maintain or restore peace. In particular, the book provides a legal analysis of the institutional mechanisms and processes which the UN employs to use force to maintain or restore peace."--BOOK JACKET.